Phenolic supplements: testing an approach to limit Sphagnum decomposition in a Sphagnum farming system - Talal Asif; Line Rochefort; Chris Freeman; Christian Dunn; Hojeong Kang; Mélina Guêné-Nanchen (Frontiers in Earth Science)
Phenolic compounds have been proposed to influence decomposition by inhibiting extracellular enzyme activities, as described in the enzymic latch mechanism (ELM). This study examined the effects of phenolic treatments on Sphagnum decomposition, productivity, and biomass accumulation within a Sphagnum farming system. A split-plot experiment with three phenolic treatments was implemented in two cultivation basins established with mosses dominated by the Acutifolia or Sphagnum subgenus. Phenolic treatments were wood pellets (wood), old roots from peat harrowing (root), and no addition (control). Phenolic additions did not result in a measurable reduction in decomposition rates nor was Sphagnum productivity or biomass affected by the experimental treatments. Both subgenera functioned as approximately similar small carbon dioxide (CO2) sinks, with values such as −2 ± 1 g CO2 m−2 d−1 (Acutifolia) and −0.2 ± 0.8 g CO2 m−2 d−1 (Sphagnum). Phenolic additions in both subgenera resulted in higher CO2 values as net ecosystem exchange compared to the control, which could be linked to emissions resulting from wood and root decomposition. In both subgenera, phenolic additions neither increased peat phenolic concentrations nor inhibited enzyme activities compared to the control. The current study did not validate the potential of phenolics in limiting decomposition as theorized in the ELM. The short duration of the experiment may have restricted the effect of phenolic products applied at the surface from reaching the ∼10 cm depth where peat was sampled. This could explain the absence of an inhibitory effect of phenolic products on enzyme activities. Therefore, it is recommended to conduct various sample analyses at different depths to better understand phenolic–enzyme interactions in a Sphagnum farming system.